Live birth rate following endometrial preparation with daily versus depot GnRH agonist - Ulas Fidan; Mustafa Ozturk; Temel Ceyhan; Lala Kazımova; Emre Karasahin (Taylor & Francis Group, 2023)
AbstractBackground Gonadotrophin-releasing hormone agonist (GnRHa) downregulates gonadotropin secretion in the pituitary gland. It is used both in ovulation induction protocols and in artificial endometrium preparation. Frozen-thawed embryo transfer to artificially prepared endometrium (FET-APE) is a frequent procedure in vitro fertilization (IVF) which requires GnRHa. It can be used either as a daily low-dose injection or as a single depot injection. It is unclear which of these two regimens is superior for artificial endometrium preparation.Methods We evaluated the data of 72 patients who had undergone frozen embryo transfer following the 5th day Preimplantation Genetic Test-aneuploidy (PGT-A) between 2018-2021. All embryos were genetically screened, and euploid single embryos were transferred. Group 1 (n: 36) used depot GnRHa, and Group 2 (n: 36) used single daily injections for artificial endometrial preparation. The outcomes for Beta Human Chorionic Gonadotrophin (BHCG) positivity and live birth rates (LBR) was compared.Results The BHCG positivity for Group 1 and Group 2 was 75% and 80.6%, respectively. The LBR for Group 1 and Group 2 were found to be 58.3% and 63.9%, respectively. There was no statistically significant differences between the two groups.Conclusions In artificial endometrium preparation, depot GnRHa offers cheaper and more convenient alternative to single daily dose injections, particularly in busy clinical settings.